Stripe rust resistance in wheat breeding lines developed for central Shaanxi, an overwintering region for Puccinia striiformis f. sp. tritici in China. Issue 3 (2nd July 2016) - Wu, J.H.; Wang, Q.L.; Chen, X.M.; Wang, M.J.; Mu, J.M.; Lv, X.N.; Huang, L.L.; Han, D.J.; Kang, Z.S.
Abstract: China is one of the largest stripe rust epidemic areas in the world. Central Shaanxi, an important overwintering region, serves as a 'bridge' between the western over-summering and eastern epidemic regions. Understanding of resistance levels and Yr- gene distribution in regional wheat breeding lines may provide valuable recommendations for releasing resistant cultivars for managing the disease. A total of 183 wheat breeding lines developed for central Shaanxi were tested for seedling resistance to nine Chinese races of Puccinia striiformis f. sp. tritici ( Pst ) in the greenhouse. In field tests, entries were evaluated for stripe rust resistance in Yangling, Shaanxi, an overwintering region for the pathogen and artificially inoculated with selected races. In Tianshui, Gansu Province, an over-summering region, entries were evaluated under natural infection of Pst . Molecular markers for Yr5, Yr9, Yr10, Yr15, Yr17, Yr18, Yr26 and Yr61 were used to determine the presence and absence of the genes. Among the 183 entries, 4 (2.2%) entries had effective all-stage resistance; 15 (8.2%) entries had adult-plant resistance; and 164 (89.6%) entries were susceptible to one or more races, especially to the potentially important races V26/CM42 and V26/Gui22. Over 95% of entries showed seedling stage susceptibility in Tianshui across years. Resistance genes Yr9, Yr17 and Yr24/Yr26 were postulated in some of the breeding lines based on the seedling responses and molecular markers. Yr5, Yr10, Yr15, Yr18 and Yr61 were not present in any of the breeding lines. These results suggest that, when multiple races of Pst disperse into Shaanxi from southern Gansu Province, over 90% of wheat breeding lines are susceptible. Based on the results, recommendations are made for releasing or not releasing the individual lines, and a strategy of combining genes for effective all-stage and adult-plant resistance is proposed for developing wheat cultivars with high-level durable resistance to stripe rust.